Pembuatan Pakan Ternak sebagai Alternatif Pemanfaatan Bonggol Jagung dan Kulit Kopi di Desa Batur Kecamatan Gading Kabupaten Probolinggo - Ahmad Sahidah (GUYUB: Journal of Community Engagement, 2020)
Batur is a village located at Gading, Probolinggo, East Java in which the recent condition of economics is dominated by agriculture and husbandry. The animal husbandry potentials of Batur include cow, goat, fowl. Meanwhile, in the agricultural sector, this village has corn, grain, coffe, vine, coconut, sugar palm tree. Based on that potentials, the training program of making the gnarl of corns and shell of coffe into the feed for animals will be necessary. The participants of the training are delegation of cattlemans in every villages of Batur, such as Klepo, Krajan, Rabunan, Tanah Merah. This program is to make sure that every delegation of the villages will be representation of the social empowerment.Keywords: Training, Feeds for Animals, Social Empowerment